Living in Peace - Shenk, David W. (Justice, Reconciliation & Peace in Africa, 1997)
It is both relevant and urgent to examine the way in which African people have struggled to cultivate justice, reconciliation and peace in their traditional life as well as in the midst of their contemporary experiences. Even though the words of justice, reconciliation and peace are strictly religious terms, the secular and religious worlds use them and need them equally. In this book, the author concentrates on the more religious dimensions of these terms. He draws from African Religion and Christianity in Africa (including Malagasy) where African religion has also been predominant. We cannot look at major religious themes in this region of Africa without taking into consideration these two religious traditions. This is a book that should be read by all concerned with justice, reconciliation and peace in Africa today.